Epstein–Barr virus in thyroid disease: an integrated immunovirological perspective - Wang, Zhengda; Chang, Xiwen; Cheng, Xianbin (Frontiers in Immunology, 2025)
Epstein–Barr virus (EBV) is a highly prevalent human herpesvirus capable of establishing lifelong latency in the host. It has garnered increasing attention for its potential pathogenic role in thyroid diseases. This review integrates current evidence linking EBV to a spectrum of thyroid diseases, including Graves’ disease, Hashimoto’s thyroiditis, thyroid cancer, and other rare subtypes. A key contribution of this work is the synthesized framework that connects viral infection, immune dysregulation, and neoplastic transformation. Unlike previous studies focused on isolated conditions, this review highlights the bridging role of EBV between autoimmunity and thyroid tumorigenesis. In addition, potential EBV-targeted therapeutic strategies are discussed, offering new perspectives for early diagnosis, risk stratification, and personalized management. Overall, this review advances the mechanistic understanding of EBV-associated thyroid diseases and provides a theoretical foundation for future research and clinical interventions.